Hydrothermal synthesis of nanostructured flower-like Ni(OH)2 particles and their excellent sensing performance towards low concentration HCN gas1. Issue 34 (15th April 2015) - Hu, Mingzhen; He, Junhui; Yang, Mingqing; Hu, Xiaochun; Yan, Chunxiao; Cheng, Zhenxing
<x xml:space="preserve">Abstract</x> Hierarchically structured Ni(OH)2 particles with a well-defined flower-like morphology were synthesized via a hydrothermal route.